Studying The Effect of Mentha Longifolia Plant Extract In Inhibition Growth of Some Bacteria and Inhibiting the Emergence Fourth Stage Larvae of Mosquitoes Aedes Aegypti (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study make as research about activity of secondary compounds in Mentha longifolia plant extracts ascrude , the effect of crude extract of Mentha longifolia leaves make as inhibitory growth factor for two typesof bacteria Staphylococcus aureus and Escherichia coli , and inhibit emerge four stage larvae of mosquitoes. watery and alcohol plant extracts of Mentha longifolia leaves were prepared , were appear variation effectin bacteria , the water plant extract show simple effect in Staph. aureus , while alcohol extract show cleareffect in E. coli . in state of emerge four stage larva of mosquitoes , there are clear effect for alcohol extractin larvae comparing with water extract